Analysis of Plant Vegetation in Sekipan Forest Tawangmangu District, Karanganyar District - Aryani, Ima; Riskawati, Shal Syabela (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
The purpose of this study was to determine the structure and composition of Vegetation structure and composition in Sekipan forest, Tawangmangu subdistrict, Karanganyar regency and to determine the tree species that dominate in the structure and composition of plant vegetation species in sekipan forest, Tawangmangu subdistrict, Karanganyar regency. This research is quantitative descriptive research. The population in this study was the vegetation in the skipan forest, Tawangmangu District, Karanganyar Regency, Central Java Province. The sample in this study is part of the area in the skipan forest, Tawangmangu District, Karanganyar Regency, Central Java Province. Method for sampling location using exploration. Data analisys using purpossive sampling. Sampling data collection for each observation using the plot sampling method. Data analysis techniques are calculated by calculating density, frequency, dominance, important value index, and diversity index. The results showed that the composition of plants in the Tawangmangu Karanganyar Sekipan Forest consisted of 52 plant species. Leucaena leucocephala has the highest density value with 110 trees/ha. The highest frequency was owned by the species Pinus Mercusii with 1.5%. The highest dominance is owned by Pinus mercusii, which is 70.95% and INP is 128.70%. A diversity index of 2.38617 indicates that diversity in sekipan forests is medium category.